Perancangan Sistem Informasi Laporan Pemeriksaan Alat Berat Berbasis Web Di PT. Ekanuri - Ima Prayudi; Shandi Noris (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Information systems and information technology is one of the factors that influence the success of an organization/company. For example, the information system used in the company PT. Ekanuri. The existing information system in PT. Ekanuri has not been efficient so that there are several obstacles in carrying out its activities. Seeing the condition of the problem, it is necessary to plan an information system that can support business processes in the company. To be able to implement the planning of information systems in accordance with the organization of course through a research. This research is a research on designing web-based heavy equipment inspection report information system. This research will use data collection methods, interviews and literature studies. This method has several analyzes, namely, entity relationship diagram (ERD), unifield modeling language (UML) design, sequence diagrams, class diagrams, interface design. From the results of this study, it will provide convenience in supporting the activities of using heavy equipment, namely making it easier to report the readiness of heavy equipment and will also speed up the reporting time for heavy equipment inspections.